DIETARY TURMERIC (Curcuma longa) ENHANCES GROWTH, ANTIOXIDANT DEFENSE, AND IMMUNITY IN Cirrhinus mrigala - Hassan, Ali; jasim, Kajeen hassan; Shahid, Ayesha; Hussein, Nizar Jalal; Azam, Hafiza Aqsa; Owais, Muhammad (Science Journal of University of Zakho, 2025)
Aquaculture is pivotal in addressing global food security, yet intensive practices compromise fish health and productivity. This study investigated the efficacy of dietary turmeric (Curcuma longa) supplementation as a natural alternative in Cirrhinus mrigala, a species critical to South Asian aquaculture. A 60-day feeding trial evaluated four diets: control (0% turmeric), 0.5%, 1.0%, and 1.5% turmeric inclusion. Results demonstrated that 1.0% turmeric significantly enhanced growth performance, with a 28% increase in final body weight (19.6 ± 1.4 g vs. 15.7 ± 1.1 g in control; p< 0.01) and improved feed conversion ratio (1.4 ± 0.2 vs. 1.7 ± 0.2; p= 0.004). Antioxidant enzyme activities (SOD, CAT, GPx) increased by 34–53%, while lipid peroxidation (MDA) decreased by 29% (p = 0.001), indicating robust oxidative stress mitigation. Immunological assays revealed a 65% rise in lysozyme activity and 70% higher phagocytic capacity (p< 0.01), underscoring turmeric’s immunostimulatory potential. The hepatosomatic index decreased by (1.3 ± 0.2% vs. 1.4 ± 0.2%; p = 0.038), suggesting increased metabolic efficiency. These findings highlight 1.0% turmeric as the optimal dosage, offering a sustainable strategy to augment aquaculture productivity while reducing reliance on antibiotics
Keywords: Curcuma longa; Growth; Antioxidant Defense; Immunity; Cirrhinus mrigala